2021
DOI: 10.3390/antibiotics10060650
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Human Peptide LL-37 as an Antimicrobial and Anti-Biofilm Agent

Abstract: The rise in antimicrobial resistant bacteria threatens the current methods utilized to treat bacterial infections. The development of novel therapeutic agents is crucial in avoiding a post-antibiotic era and the associated deaths from antibiotic resistant pathogens. The human antimicrobial peptide LL-37 has been considered as a potential alternative to conventional antibiotics as it displays broad spectrum antibacterial and anti-biofilm activities as well as immunomodulatory functions. While LL-37 has shown pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(82 citation statements)
references
References 210 publications
(467 reference statements)
0
82
0
Order By: Relevance
“…Bacterial lysis occurs due to altered permeability of the bacterial membrane with transmembrane pores [22]. In fact, LL-37 showed a broad-spectrum against several different pathogens, such as Gram-positive and Gram-negative bacteria [23], fungi [24][25][26] and viruses [27]. Moreover, LL-37 revealed other biological activities, such as regulation of responses to inflammation, showing both pro-inflammatory and anti-inflammatory effects [28].…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial lysis occurs due to altered permeability of the bacterial membrane with transmembrane pores [22]. In fact, LL-37 showed a broad-spectrum against several different pathogens, such as Gram-positive and Gram-negative bacteria [23], fungi [24][25][26] and viruses [27]. Moreover, LL-37 revealed other biological activities, such as regulation of responses to inflammation, showing both pro-inflammatory and anti-inflammatory effects [28].…”
Section: Introductionmentioning
confidence: 99%
“…Mutants lacking HacA in Aspergillus fumigatus and Hxl1 in Cryptococcus neoformans , the homologs of Hac1, attenuate virulence in mouse models of infection [ 71 , 72 ]. LL-37 is a multifunctional AMP commonly found at mucosal surfaces of humans and plays an important role in the first line of defense against microbial infection [ 17 , 73 ]. Our previous studies showed that LL-37 targets the cell wall and affects C. albicans adhesion to abiotic and biotic surfaces, including oral epidermal cells and mouse bladder mucosa [ 19 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mannosides target the bacterial adhesin of FimH to prevent infection by reducing bacterial colonization via adhesion suppression [75]. LL-37 is a cathelicidin-derived broad spectrum antimicrobial peptide that has been investigated to restrain biofilms by preventing bacterial attachment to the surface [76]. LL-37 also displays broad spectrum antibacterial activities and immunomodulatory functions.…”
Section: Treatment Strategies For Biofilm Eradicationmentioning
confidence: 99%